Lemahnya Manajemen Lembaga PAUD: Antara Orientasi Operasional dan Pengabaian Mutu Pendidikan serta Solusi Penanggulangan - Andika, Dira Meri (Jurnal Pendidikan Dirgantara, 2025)
Early Childhood Education (PAUD) plays a fundamental role in shaping children's character, moral values, and intellectual potential from an early age. However, many PAUD institutions in Indonesia still face serious challenges in management, where attention is focused more on operational sustainability than on improving educational quality. This study aims to describe the actual condition of PAUD institutions, analyze the causes of weak management, and identify the impact of operational orientation on educational quality. The method used is a literature study through analysis of various sources such as books, scientific journals, research reports, and government policies related to PAUD implementation. The results of the study indicate that weak management is caused by limited human resources, low managerial competence, minimal funding, weak planning, and a lack of supervision and community support. The impact is seen in the decline in educational quality and low public trust in PAUD institutions. Therefore, it is necessary to strengthen quality-based management that emphasizes improving educator competence, community involvement, effective management of infrastructure, utilization of educational technology, and implementation of continuous evaluation. Professional and adaptive PAUD management is key to realizing superior, high-quality institutions that are relevant to the developmental needs of early childhood in the modern era.